PENGARUH PEMBERIAN EKSTRAK CABAI RAWIT (Capsicum frustescens L.) TERHADAP GAMBARAN HISTOLOGI ORAL SQUAMOUS CELL CARCINOMA (STUDI IN VIVO) - Pratiwi Nur Widyaningsih; Fitri Aniowati; Cantika Nadrotan Naim; Nova Dwi Anggraeni (Fakultas Kedokteran Universitas Jenderal Soedirman, 2021)
Oral squamous cell carcinoma (OSCC) is a cancer of the oral cavity that is often associated with a low life expectancy. OSCC is a multifactorial disease, and its symptoms typically manifest as ulceration with exophytic and persistent edges. Cisplatin is a commonly used chemotherapeutic agent for treating OSCC, but it has high toxicity. Cayenne pepper (Capsicum frutescens L.) is a widely consumed plant that contains capsaicin, which can act as an anticancer agent by increasing p53 antibodies in the apoptosis process, thereby preventing cancer cell proliferation and degrading p53 gene mutations. This study aims to determine the effect of administering cayenne pepper extract (Capsicum frutescens L.) on the histological features of oral squamous cell carcinoma (in vivo study). Thirty male Wistar rats, aged 2 months and weighing 150-200 grams, were divided into five groups: negative control group (K-) without treatment, positive control group (K+) given DMBA exposure, treatment group with DMBA exposure and cisplatin induction, treatment group with DMBA exposure and induction of gel nanoparticles containing 1% capsaicin extract, and treatment group with DMBA exposure and induction of gel nanoparticles containing 3% capsaicin extract. The data were analyzed statistically using the One-Way ANOVA test followed by Post hoc LSD. The results showed significant differences (P<0.05) among all groups, except between KP1 and KP2, KP3 and K+, and KP1 and KP-. The administration of 1% capsaisen nanoparticle gel had a similar effect to cisplatin administration in terms of the number of mitoses and atypical cells under OSCC conditions.